The Implementation of the STAD Method to Improve Narrative Writing Skills of Seventh-Grade Students - Utari, Utari; Arini Vika Sari (PT. Mifandi Mandiri Digital, 2024)
This study aims to improve the narrative writing skills of seventh-grade students at MTs Alwasiyah Pantai Labu through the implementation of the STAD (Student Teams Achievement Divisions) learning method. The research was conducted as a Classroom Action Research (CAR) over two cycles, each comprising one meeting, involving 22 students as research participants. The study employed the Kemmis and McTaggart model, utilizing observation, written tests, and documentation as data collection techniques. Data were analyzed using descriptive statistical methods by calculating the class average scores. The success criteria were set at a minimum class average score of 70 and at least 80% of students achieving mastery learning. The results indicated that the pre-action average score was 64.7 with 8 students not achieving mastery, which improved to 73.4 in the second cycle with only 3 students not achieving mastery. These findings demonstrate that the application of the STAD method effectively enhances students’ narrative writing skills and their learning motivation.